Mitochondria-Targeted Liposomes for Drug Delivery to Tumor Mitochondria - Aysegul Ekmekcioglu; Ozgul Gok; Devrim Oz-Arslan; Meryem Sedef Erdal; Yasemin Yagan Uzuner; Meltem Muftuoglu (MDPI AG, 2024)
The special bilayer structure of mitochondrion is a promising therapeutic target in the diagnosis and treatment of diseases such as cancer and metabolic diseases. Nanocarriers such as liposomes modified with mitochondriotropic moieties can be developed to send therapeutic molecules to mitochondria. In this study, DSPE-PEG-TPP polymer conjugate was synthesized and used to prepare mitochondria-targeted liposomes (TPPLs) to improve the therapeutic index of chemotherapeutic agents functioning in mitochondria and reduce their side effects. Doxorubicin (Dox) loaded-TPPL and non-targeted PEGylated liposomes (PPLs) were prepared and compared based on physicochemical properties, morphology, release profile, cellular uptake, mitochondrial localization, and anticancer effects. All formulations were spherically shaped with appropriate size, dispersity, and zeta potential. The stability of the liposomes was favorable for two months at 4 °C. TPPLs localize to mitochondria, whereas PPLs do not. The empty TPPLs and PPLs were not cytotoxic to HCT116 cells. The release kinetics of Dox-loaded liposomes showed that Dox released from TPPLs was higher at pH 5.6 than at pH 7.4, which indicates a higher accumulation of the released drug in the tumor environment. The half-maximal inhibitory concentration of Dox-loaded TPPLs and PPLs was 1.62-fold and 1.17-fold lower than that of free Dox due to sustained drug release, respectively. The reactive oxygen species level was significantly increased when HCT116 cells were treated with Dox-loaded TPPLs. In conclusion, TPPLs may be promising carriers for targeted drug delivery to tumor mitochondria.